2007
DOI: 10.1021/bc0700178
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide Carrier to Effectively Deliver Native Phosphodiester CpG DNA to Antigen-Presenting Cells

Abstract: Oligodeoxynucleotides containing unmethylated CpG sequences (CpG DNAs) activate the vertebrate innate immune system via toll-like receptor 9 (TLR-9). Although CpG DNA is a promising immunotherapeutic agent, its short circulation time in biological fluids due to nuclease is the major drawback. This paper proposes that a natural polysaccharide called schizophyllan (SPG) can be used as an effective CpG DNA carrier because SPG can complex with CpG DNA and the resultant complex shows the nuclease resistance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In this study, we generated a novel K CpG ODN that we designated K3-SPG. Although it had been reported that there are molecular interactions between single-stranded nucleic acids and β-glucan (37) and that murine and humanized CpG ODNs can be wrapped by SPG to increase their original TLR9-agonistic activities (20), our report demonstrates that a rod-shaped nano-sized K3-SPG particle exhibits dual characteristics of K and D CpG ODNs (Fig. 1).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, we generated a novel K CpG ODN that we designated K3-SPG. Although it had been reported that there are molecular interactions between single-stranded nucleic acids and β-glucan (37) and that murine and humanized CpG ODNs can be wrapped by SPG to increase their original TLR9-agonistic activities (20), our report demonstrates that a rod-shaped nano-sized K3-SPG particle exhibits dual characteristics of K and D CpG ODNs (Fig. 1).…”
Section: Discussionmentioning
confidence: 56%
“…To make a complex between CpG ODNs and schizophyllan (SPG), CpG ODNs need additional sequences of phosphorothioate backbone of 40-mer polydeoxyadenylic acid (dA 40 ) at the 5′ or 3′ end (20,22). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharides used in this study are; i) naturally occurring, readily available, easily extracted in bulk ii) cheap iii) does not require sophisticated formulation technology as it is water soluble iv) readily undergoes stable interaction with charged Recent studies showed that a natural b-glucan polysaccharide isolated from Schizophyllan modified with peptides and cholesterol formed a complex with TLR9 ligand, CpG ODNs and significantly elevated secretion of cytokines (IL12, IL6 and TNFa) from BMDCs, and murine macrophages [27,28]. These compounds were proposed to trigger several immune cells through various receptors including complement receptor (CR3), scavenger receptors, as well as TLR4 or TLR2/6 [29e32].…”
Section: Discussionmentioning
confidence: 99%
“…When the complex of native SPG and CpG DNA (s-SPG/CpG DNA) was added, its secretion was increased by about 20-40% compared with that of the naked dose. 67 This increment can be ascribed to the SPG-mediated protection from the nucleasemediated hydrolysis. The CpG DNA complexed with the chemically modified SPG-derivatives increases the cytokine secretion remarkably, i.e., five-to ten-fold compared with that of the naked dose.…”
Section: Application Of the Complex To An Odn Delivery Vehiclementioning
confidence: 99%